Pengaruh Model PBL Berbantuan Media Audiovisual Powtoon terhadap Kemampuan Berpikir Kritis Siswa - Rahayu, Dini Sela Widia; Ratnasari, Ratnasari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine the effect of the PBL model assisted by POWTOON audiovisual media on the critical thinking skills of fourth-grade students in Tulung Sari State Elementary School in the material of mixed number arithmetic operations. The research method used in this study is the experimental method and the form of research design used in this study ispre-experimental design (non design) with desain one group pretest-posttest design.The results of the study showed that there was a significant difference between the resultspretest And posttest after the implementation of the PBL model assisted by the POWTOON audiovisual media.This can be seen from the results of the normality test, which obtained the following significant results:pretest0.113 > 0.05 is normally distributed and the resultsposttest0.231 > 0.05 is normally distributed while the test resultspaired sample t-testobtained a significance value of 0.000 which is smaller than 0.05. Therefore, H0 rejected and H1 accepted, namely showing that there is an influence of the PBL model assisted by audiovisual media POWTOON on the critical thinking skills of fourth grade elementary school students. And based on the N-Gain test, the results obtained were 0.6356, where the value of 0.6356 is in the